THE ROLE OF VIRTUAL ULAMA EXPOSURE IN ISLAMIC BANKING INTENTIONS AMONG INDONESIAN MUSLIM YOUTH - sumaiya, Naili; Mansor, Fadillah; Mandalia, Siska; Haridhi, Hafiz Mubarraq (Universitas Islam Negeri Alauddin Makassar, 2026)
Purpose - This study investigates the determinants of Islamic banking intention among Indonesian Muslim youth by examining the effects of wasatiyya values, Islamic financial literacy, and exposure to virtual ulama. Methods - A quantitative cross-sectional survey was conducted using an online questionnaire. Of the 309 responses collected, 103 valid responses were retained after systematic screening and data-cleaning procedures. Multiple linear regression was employed to examine the relationships between the independent variables and Islamic banking intention. Findings - The findings indicate that exposure to virtual ulama has a significant positive influence on Islamic banking intention, whereas wasatiyya values and Islamic financial literacy do not exhibit significant direct effects. These results suggest that digitally mediated religious authority plays a more influential role than ethical orientation and financial knowledge in shaping Islamic banking intention among Muslim youth. Research Implications - The study implies that policymakers, Islamic financial institutions, and educators should strengthen collaboration with credible digital religious influencers to enhance Islamic financial awareness and promote Islamic banking adoption. Originality - The originality of this study lies in integrating virtual ulama exposure with Islamic financial literacy and wasatiyya values to explain Islamic banking intention within the context of Indonesian Muslim youth.